Manual de procedimentos do Programa Subsídio Social Básico (PSSB) - INAS - Instituto Nacional de Acção Social (2022)
O presente Manual de Procedimentos (MdP) apresenta a definição do Programa Subsídio Social Básico (PSSB), os objectivos, as componentes, os grupos-alvo, os critérios de elegibilidade, os tipos de benefícios, os mecanismos e frequência de pagamentos, a permanência de beneficiários no programa e formas de saída, a transferência de beneficiários entre componentes do programa, bem como o seu ciclo operacional. Para além dos Guiões práticos que oferecem descrições detalhadas de cada processo a ser desenvolvido por todos os actores da implementação do PSSB, o Manual tem como objectivo orientar aos intervenientes e uniformizar os procedimentos a adoptar na implementação do PSSB.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental

Anuário Estatístico - Statistical Yearbook 2021 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2022)
As in previous editions, the Statistical Yearbook 2021 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2017-2021 series. The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Getting Real about Unknowns in Complex Policy Work - Andrews, Matt (Research on Improving Systems of Education (RISE), 2021)
As with all public policy work, education policies are demanding. Policy workers need to ‘know’ a lot—about the problems they are addressing, the people who need to be engaged, the promises they can make in response, the context they are working in, and the processes they will follow to implement. Most policy workers answer questions about such issues within the structures of plan and control processes used to devise budgets and projects. These structures limit their knowledge gathering, organization and sense-making activities to up-front planning activities, and even though sophisticated tools like Theories of Change suggest planners ‘know’ all that is needed for policy success, they often do not. Policies are often fraught with ‘unknowns’ that cannot be captured in passive planning processes and thus repeatedly undermine even the best laid plans. Through a novel strategy that asks how much one knows about the answers to 25 essential policy questions, and an application to recent education policy interventions in Mozambique, this paper shows that it is possible to get real about unknowns in policy work. Just recognizing these unknowns exist—and understanding why they do and what kind of challenge they pose to policy workers—can help promote a more modest and realistic approach to doing complex policy work.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); education / educação; government policy / politica governamental

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Rural Observer, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

A Guide to Assessing the Political Economy of Domestic Climate Change Governance - Worker, Jesse; Palmer, Niki (World Resources Institute, 2021)
This paper discusses how understanding the domestic political economy of climate governance is critical for developing informed strategies to build and sustain political ambition. It provides guidance and a methodology for domestic stakeholders to determine the types of institutional reforms, incentives, coalitions, and policy design that can entrench long-term political support for climate ambition. The assessment can also help users identify political barriers to more equitable climate action and identify reforms that may strengthen inclusion and accountability. EXECUTIVE SUMMARY Highlights ▪ There is overwhelming evidence of the social, economic, and environmental case to reduce greenhouse gas (GHG) emissions and rapidly scale up adaptation. Yet, despite a proliferation of climate laws and policies over the last 10–15 years, emissions are still rising, and adaptation needs remain urgent. ▪ This calls for a more sophisticated assessment of the political economy factors that may enable or constrain implementation of policies and actions and sustain political commitment at the country level. ▪ This guide offers an assessment methodology to understand how structural factors, rules and norms, stakeholders and interests, and ideas and narratives influence the political economy of climate action in a given country context. ▪ The methodology was developed on the basis of climate policy, governance, and political economy literature with contributions from subject matter experts. ▪ We intend the assessment to support civil society coalitions, reform-minded civil servants and politicians, international organizations, and other stakeholders. ▪ The resulting analysis should deepen the understanding of context while informing the advocacy, policy design, coalition building, capacity building, and communications of domestic stakeholders.
Keywords: #Reviews & Framing / Revisões e Organização; L - english / inglês; M - methodology / metodologia; M - political economy analysis (PEA) / análise de economia política (AEP); governance / governação

Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

Anuário Estatístico - Statistical Yearbook 2020 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2021)
As in previous editions, the Statistical Yearbook 2020 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2016-2020 series The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Agrário Integrado 2020 - MADER (República de Moçambique - Ministério da Agricultura e Desenvolvimento Rural Direcção de Planificação e Políticas (DPP), 2021)
O crescimento agrícola em Moçambique é uma fonte essencial para promover o crescimento económico do País em geral e das famílias rurais em particular. O Programa do Governo para o Sector Agrário, em harmonia com a política económica do País, orienta-se para o alcance de grandes objectivos estratégicos, nomeadamente: (1) Segurança Alimentar; (2) Aumento do Rendimento Familiar; (3) Criação de Emprego/Inclusão Social e (4) Aumento da Produção e Produtividade. Este documento ilustra, de forma simples e clara, a situação e a dinâmica da agricultura em Moçambique durante o ano de 2020. O Inquérito Agrário Integrado (IAI 2020), indica que existem no país cerca de 4.3 milhões de explorações agro-pecuárias, das quais 4.167.702 (97.8%) são pequenas, 93.183 (2%) são médias, e 873 (<1%) são grandes explorações. Do total de cerca de 4.3 milhões de explorações (Pequenas e Médias), cerca de 6.9% receberam informação ou conselho técnico de extensão, 39.9% tiveram acesso à informação sobre preços e 0.6% acesso à crédito. A área cultivada foi de cerca de 5.5 milhões de hectares, onde 5.5% das explorações utilizaram pesticidas nos seus campos, 8.8% usaram estrume, 7.8% utilizaram fertilizantes químicos e 9.1% usou a rega. As principais culturas em diversas explorações são o Milho, Arroz, Mapira, Amendoim Pequeno, Feijão Nhemba, Feijão Boer, Mandioca, Algodão e Canade-açúcar. Grande parte das explorações cultivam Milho (83.8%), 23.6% Amendoim Pequeno, 18.3% Mapira, 12 .8% Arroz e 3.8% Mexoeira. O IAI 2020, realizado pela primeira vez com referencial distrital, é um Marco Estatístico e principal fonte de dados do sector agro-pecuário, assim como marco amostral, pois fornece dados fiáveis desagregados até ao nível Distrital, para apoiar o processo de planificação e tomada de decisão a todos níveis, baseadas em evidências científicas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura; demographics / demografia

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Project for Construction of Bridges on N380 in Cabo Delgado - JICA (2020)
Project outline Project Overview： - This project is to secure smooth and safe connectivity at the road N380 (Sunate - Oasse) through reconstruction of bridges, Messalo1 (45m)/ Messalo-3 (60m)/ Mapuede (45m), thereby contributing to facilitate the economy of Cabo Delgado and neighboring countries
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; infrastructure / infrastrutura

Mozambique: Analytical Report on Decentralisation - Salimo, Padil (Asociação Nacional de Municipios de Mozambique - ANAMM, EU and UCLG Africa, 2020)
The United Cities and Local Governments of Africa (UCLGA) commissioned this report in coordination with the National Association of Municipalities of Mozambique (ANAMM) to analyse the political economy of decentralisation of Mozambique. The report provides information in support of the ANAMM discussion and dialogue toward the new European Union (EU) programming process of cooperation with local authorities (LAs) for the 2021-2027 period. This report was developed in line with another called “Compendium of References” which is also part of the preparation for the EU programming process of cooperation with the Las. The analytical report on political economy pretends to explore the extent to which the central government embraced the conceptualisation of territorial development, the level of commitment of central government in recognizing the role of local authorities in the territorialisation of the national development agenda, and the opportunities and constraints created by the decentralisation system for the empowerment of local authorities as developmental actors. The political economy analysis catches the key aspects of how political and economic power influences the way how decentralisation is implemented and contested, the incentives behind the political actors and interests groups and how they impact the decentralisation reforms outcomes. The report serves as a background document to a seminar of the members of the ANAMM, which is part of a process of building consensus over the key priority action to include in the municipalities’, or interchangeably called in the report also as local authorities, roadmap for dialogue with the central government and the EU Delegation in Maputo, Mozambique. The expected result involves the following: (i) An analysis of the political economy of decentralisation, the feasibility of the new local authorities (LAs) driven political agenda and the opportunities and constraints created by the decentralisation reforms; (ii) An overview of the state of art regarding the territorialising of national policies and global agendas including SDGs, in terms of both policies and programs adopted in the framework of the national development plan; (iii) A SWOT quick analysis of the ANAMM; and (iv) The state of the art concerning the territorialisation of national policies and global programs, including Sustainable Development Goals (SDGs), both at the level of policies and programs implemented within the framework of the National Development Plan.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Mozambique Crisis Response Plan 2020 - IOM - International Organisation for Migration (IOM - International Organisation for Migration, 2020)
The overall objective of IOM's strategy is to support displaced persons and other affected populations in Mozambique to build resilience and progress towards sustainable solutions to displacement while ensuring a continuous response to critical humanitarian needs and rapid response capacities in case of a new disaster and crisis. Recovery and resilience in Mozambique will be facilitated through an effective and locally owned framework that addresses the lifesaving and longer-term needs of affected populations. Ultimately, the plan aims at establishing the basis for recovery and crisis prevention in communities and continuing being a key partner of the Government of Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; displaced communities / comunidades deslocadas

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

Depois da ADIN, Celso Correia “ganha” Agência do Zambeze e passa a controlar o desenvolvimento do centro e norte de Moçambique - Nuvunga, Adriano (Centro para a Democracia e Desenvolvimento (CDD), 2020)
Tal como procedeu no caso da passagem da tutela da ADIN para Celso Correia, o CDD defende que a Agência do Zambeze deve estar sob tutela do Conselho de Ministros e a sua direcção deve prestar contras ao Primeiro-Ministro. À semelhança da ADIN, a Agência do Zambeze tem uma visão holística de desenvolvimento e uma actuação transversal que abrange todos os sectores económicos e sociais do Governo, pelo que não faz sentido a sua direcção responder a um Ministro responsável por um único sector, seja ele de Economia ou de Desenvolvimento. Pela sua importância estratégica para o desenvolvimento do pontecial do Vale do Zambeze, a Agência do Zambeze deve ser dirigida por gestores de reconhecido mérito recrutados através por um concurso público transparente e independente, como forma de evitar a gestão danosa e as infracções financeiras denunciadas pelo Tribunal Administrativo em 2018. Quando o Governo de Armando Guebuza criou a Agência do Zambeze em 2010, o objectivo principal era de “assegurar a eficácia e a eficiência no desenvolvimento da parte nacional da bacia hidrográfica do Vale do Rio Zambeze, uma das regiões cujo potencial de recursos e as possibilidades de aproveitamento estudadas apontam como susceptível de, rapidamente, contribuir para o desenvolvimento e crescimento económico e humano auto-sustentado do país”. Volvidos 10 anos depois, a Agência do Zambeze ainda não deu sinais de estar a explorar as potencialidades do Vale do Zambeze para dinamizar o desenvolvimento das províncias do centro do país, que concentram boa parte da população pobre de Moçambique. O Vale do Zambeze tem potencial energético, grandes depósitos de minerais como carvão e ferro, para não falar do potencial agro-pecuário subaproveitado. Não foi por acaso que o político português Almeida Santos uma vez declarou: “Quem tem o Vale do Zambeze não pode ser um país pobre”6. Mas os cerca de 12 milhões de pessoas que vivem nas quatro províncias atravessadas pelo Vale do Zambeze continuam num vale de pobreza.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; rural development / desenvolvimento rural

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Mozambique Political Process Bulletin 58, 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Niassa, Mozambique: The Makhuwa-Shirima and Yao Peoples - Center for the Study of Global Christianity (Gordon-Conwell Theological Seminary, 2020)
The region of modern-day Mozambique has always been strategic for global trade. Since at least the medieval period its coasts have been visited by traders from India, Somalia, Ethiopia, and beyond. Portuguese explorer Vasco da Gama arrived in 1498, marking the beginning of nearly 500 years of Portuguese colonial rule of the territory. Mozambique achieved independence from Portugal in 1975, but subsequently experienced a series of civil wars from 1977 to 1992. Democratic elections in 1994 resulted in a relatively stable modern republic. Despite the history of power struggles, Mozambique’s indigenous population, which include the Yao and the Makhuwa-Shirima peoples, carries with it a unique legacy challenged by colonialism and trade. To the present-day, these peoples maintain a presence in Mozambique; albeit, one that is continually threatened by cultural imperialism and globalization. The Yao (also, Wayao) people, many of whom live in Niassa province, largely rejected foreign colonial rule and the Christianity associated with it. Islam, introduced by Arab traders, was perceived a better cultural fit for the Yao and allowed for greater economic opportunities in light of the extant slave trade that ran through the Lake Niassa region and along the Rovuma River. As a result, the Yao were quite prosperous. Famous Scottish pioneer missionary-explorer David Livingstone passed through Niassa in search of the most direct route to the African interior. One of his most trusted African colleagues was a Yao man.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; society / sociedade

‘Demonstration fields’, anticipation, and contestation: agrarian change and the political economy of development corridors in Eastern Africa - Chome, Ngala; Gonçalves, Euclides; Scoones, Ian; Sulle, Emmanuel (Journal of Eastern African Studies, 2020)
In much of Eastern Africa, the last decade has seen a renewedinterest in spatial development plans that link mineralexploitation, transport infrastructure and agriculturalcommercialisation. While these development corridors haveyielded complex results–even in cases where significantinvestments are yet to happen–much of the existing analysiscontinues to focus on economic and implementation questions,where failures are attributed to inappropriate incentives or lack of‘political will’. Taking a different–political economy–approach,this article examines what actually happens when corridors‘hitthe ground’, with a specific interest to the diverse agriculturalcommercialisation pathways that they induce. Specifically, thearticle introduces and analyses four corridors–LAPSSET in Kenya,Beira and Nacala in Mozambique, and SAGCOT in Tanzania–which are generating‘demonstrationfields’, economies ofanticipation andfields of political contestations respectively, andas a result, creating–or promising to create–diverse pathwaysfor agricultural commercialisation, accumulation anddifferentiation. In sum, the article shows how top-down grand-modernist plans are shaped by local dynamics, in a process thatresults in the transformation of corridors, from exclusivist‘tunnel’visions, to more networked corridors embedded in localeconomies, and shaped by the realities of rural Eastern Africa.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Análise de Economia Política da Governação Local Moçambique - Eurosis (Mozambique Monitoring and Evaluation Mechanism and Services (MMEMS), 2020)
A governação local em Moçambique continua a desenvolver-se em duas vertentes: a desconcentração de poderes, através dos órgãos locais do Estado (secretarias de Estado da província, administrações distritais, etc), e a devolução do poder através dos órgãos de poder local (presidentes de conselhos autárquicos e governadores provinciais eleitos). O processo de criação de autarquias tem sido muito lento e a maioria dos cidadãos vive em áreas geridas pelos órgãos locais do estado e não por órgãos eleitos directamente por si. Não é ainda claro como vai funcionar a administração pública no novo figurino que criou a representação do Estado nas províncias onde existem governadores eleitos e um governo estabelecido. O que é claro, é a forte tendência para a centralização do partido político no poder e para a intervenção directa na gestão local da coisa pública, o que afecta a inclusão, transparência e prestação de contas em todas as áreas de governação. O quadro de políticas e legal é disperso e omisso em relação a como se realiza a participação dos cidadãos e cidadãs na governação em geral e como se promove a inclusão, transparência e prestação de contas. É também limitado o quadro em que operam serviços fundamentais para a transparência da administração pública, como por exemplo, os serviços de inspecção de saúde e educação, cujo quadro regulatório limita o potencial destas intervenções. Este contexto cria oportunidades para o exercício de poder discricionário a todos os níveis e leva a que intervenções fiquem dependentes do interesse político dos líderes aos vários níveis para a sua implementação. Num contexto de uma corrupção generalizada, isto é um obstáculo à realização de actividades e sustentabilidade das intervenções. Apesar das limitações apontadas, existem oportunidades e espaços para promover uma maior participação dos cidadãos e melhor prestação de contas do sector público, os quais podem ser usados como base para novas intervenções. Assim, apesar da ausência de um bom quadro legal, há alguma legislação e posições públicas do governo que remetem para um primado do cidadão, para um serviço público de qualidade e inclusivo e para o combate à corrupção. Há também mecanismos e processos que assumem a participação informada dos cidadãos nos processos de decisão sobre questões do desenvolvimento em geral (IPCC, assembleias autárquicas e provinciais) e da saúde e educação em particular (comités das unidades de serviços). Existem formalmente instituições e processos que têm como função garantir uma administração pública isenta e de qualidade (inspecção, tribunais administrativos provinciais, gabinetes anticorrupção). O nível de funcionamento destes mecanismos e processos varia muito e está dependente do interesse dos governantes locais, da mobilização comunitária e dos recursos existentes). Assim, pode dizer-se que há uma base para sobre a qual trabalhar para conseguir mais transparência, prestação de contas e inclusão ao fortalecer a governação local ao nível provincial, distrital e local (da unidades de prestação se serviços). Também o apoio à inspecção de saúde e educação pode contribuir para a melhoria da qualidade de serviços prestados aos cidadãos ao assegurar um melhor seguimento das regras e protocolos de prestação de serviços. É importante notar, contudo, que para além dos obstáculos acima referidos, o presente momento coloca desafios particulares ao desviar a atenção do governo para a resposta aos conflitos armados e à pandemia do COVID-19.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; GP - Nampula; GP - Zambézia; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; education / educação; governance / governação; health / saúde; institutions / instituições

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, João, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Anuário Estatístico da Província de Nampula 2019 - INE (Instituto Nacional de Estatística, Governo de Moçambique, 2020)
O Anuário Estatístico da Província de Nampula 2019 é uma publicação estatística de carácter geral que a Delegação do Instituto Nacional de Estatística em Nampula leva aos utilizadores e ao público em geral, como um vínculo para a disseminação dos principais indicadores económicos, sociais e demográficos da Província.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Indicadores Básicos de Agricultura e Alimentação 2015-2019 - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística (INE), 2020)
1. Esta publicação apresenta os indicadores básicos de agricultura e alimentação dos últimos 5 anos, como alternativa da base de dados na plataforma online “countryStat” produzida com fontes administrativas, mas descontinuada em 2019. A publicação não abrange todos indicadores cobertos como desejado, porque alguns requerem harmonização metodológica e outros ainda não são produzidos com regularidade pelos sectores. 2. A compilação desta publicação baseou-se na recolha e tratamento preliminar das bases de dados disponibilizadas pelas fontes administrativas dos sectores. A seguir, a equipa de produção fez a limpeza e validação de dados, resultando na publicação com 10 grupos de indicadores. 3. Nos indicadores socio-demográficos, destaca-se a população de Moçambique, como principal activo da produção, ao atingir a magnitude de 29,3 milhões de habitantes em 2019, 66,2% da qual vivia na área rural, e continuando concentrada em Nampula e Zambézia com 6,03 e 5,43 milhões de habitantes respectivamente. 4. O segundo indicador refere-se à insegurança alimentar aguda, cujo resultado indica um grande agravamento, ao partir de 3,6% em 2013 para 29,9% de famílias em 2019, um comportamento assumido também pela desnutrição aguda em crianças que de 1,9% em 2013 deteriorou-se para 12,3% em 2019. 5. Nos indicadores económicos, ressalta o peso do PIB do sector agrário a preços constantes, ano base de 2014, que estabilizou-se em torno de 23%, entre 2015 e 2019, tendo a respectiva taxa de crescimento registado 1,2% em 2019, abaixo da média nacional que foi de 2,3% face a 2018. O orçamento do estado alocado ao sector continuou abaixo de 10% em todo quinquénio, tendo-se fixado em 4,9% em 2019 6. A mecanização agrícola, medida pelo número de tractores alocados pelo Fundo do Desenvolvimento Agrário ao sector privado para agricultura familiar, reduziu, ao partir de 361 em 2015 para 26 unidades em 2019. No entanto, a área lavrada pelos provedores deste serviço e os produtores beneficiados aumentaram 97% e 781% respectivamente entre 2015 e 2019. 7. O crédito concedido ao sector agrário manteve-se insignificante se comparado com o resto da economia ao corresponder a um peso de 3,65% em 2015 e 3,71% em 2019. 8. A produção per capita de cereais continuou baixa para garantir a segurança alimentar, ao registar 71(Kg/hab) em 2015 e 94,3 kg em 2019. Para mandioca e batata doce, a situação continuou bem e melhor com a produção per capita de 267 kg em 2015 e 336 kg em 2019. A produção das culturas de rendimento foi estável no período de referência, facto observado nas mudas de cajueiros produzidas em torno de 4,5 milhões em 2019. Os produtos pecuários apresentaram, ao longo do quinquério, valores per capita baixos. Com efeito, a carne de frango registou uma produção per capita de 3,8 kg em 2019, partindo de 2,5 kg em 2015. Na produção de carne bovina, destacou-se a Província de Maputo com quase a metade da produção do País, 7 266 toneladas em 2019. Manica e Sofala destacaram-se na produção de leite de vaca ao deter 41,3 % e 25,1 % do total em 2019, respectivamente. A produção de pescado per capita caiu para 11,6 em 2019, depois de 13,7 kg em 2018 e 12,4 kg em 2017. Contudo, ressalta-se a produção de peixe marinho com 177 071 toneladas em 2019 correspondentes a 59,5% de toda a produção do sector. 9. No comércio externo, evidencia-se a exportação de açúcar e produtos de confeitaria, com crescimento de 22,9% da contribuição na receita aduaneira de 2019.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - indicators / indicadores; Northern PEA; agriculture / agricultura

Campanha Agrícola 20/21: Mais de 300 mil hectares lavrados na campanha agrícola 2020/21 - MADER (Agricultura, 2020)
Mais de 300 mil hectares lavrados na campanha agrícola 2020/21
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

Protecção Social e Os Principais Obstáculos ao Financiamento das Empresas Através da Bolsa de Valores de Moçambique - Siúta, Moisés; Chishte, Ussene (Desafios para Moçambique 2020, 2020)
O objectivo deste artigo é discutir o papel da Bolsa de Valores de Moçambique como uma das vias que mobiliza financiamento para as empresas moçambicanas tendo em conta as barreiras explícitas e implícitas que tanto a Bolsa como as empresas enfrentam no desempenho das suas funções no mercado financeiro em particular e na economia moçambicana em geral. A consecução deste objectivo está associada à de outros três objectivos específicos. Primeiro, estabelecer o quadro teórico dentro do qual a relação entre a Bolsa de Valores e as empresas pode ser discutida. Segundo, descrever o contexto em que a Bolsa de Valores e as empresas moçambicanas operam. Por fim, terceiro, discutir a forma como os principais desafios do ambiente económico nacional, enfrentados pela Bolsa e pelas empresas, afectam o acesso a financiamento, o crescimento e o desenvolvimento das empresas moçambicanas. O presente artigo está divido em seis secções incluindo a presente introdução. A segunda secção, estabelece a relação entre a protecção social e o financiamento das empresas. A terceira e a quarta secções procuram enquadrar a Bolsa de Valores conceptual e teoricamente. A quinta secção apresenta as características dos principais intervenientes no sistema financeiro nacional destacando os principais aspectos que contribuem para a compreensão dos principais obstáculos ao financiamento das empresas e da população no contexto económico actual. A sexta secção discute os obstáculos ao financiamento das empresas no sistema financeiro com foco particular para a sua relação com a Bolsa de Valores de Moçambique. Por fim, a sétima secção apresenta as considerações finais, sintetizando a relação entre a protecção social e o financiamento às empresas e realçando a importância das empresas no crescimento e desenvolvimento da actividade económica do País, assim como na geração de emprego para o bem-estar da população. Adicionalmente, a mesma secção faz uma breve reflecção sobre a maneira como a política pública tem contribuído negativamente para o financiamento das empresas privadas nacionais.
Keywords: *indexed; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; Social Protection PEA; social protection / proteção social

Walking the talk?: A critical perspective on sustainable peace and reconciliation in Mozambique - Weimer, Bernhard (Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, 2020)
The August 2019 Maputo Accord on Peace and Reconciliation appears not to be standing on entirely solid ground. Not only has the decentralization agreement suffered from last minute ‘adulteration’, but also the DDR process has been lacking speed and rigour. The circumstances and outcomes of the October 2019 elections have cast doubt on the extent to which Renamo will abide to the August 2019 agreement. The party appears to be split on the matter of the – officially disowned armed Junta Militar maintaining low-intensity, nevertheless deadly, attacks on civilian traffic in central Mozambique. Thus it remains doubtful at the beginning of 2020 to what extent the ambitious DDR process, the key Pillar/Provision of the most recent peace agreement, may be implemented and by when. Further, the institutional setup of the Peace Secretariat and the donor-financed MDTF for DDR process leave doubts about national ownership of and responsibility for the implementation of the Peace Agreement, which uses reconciliation as a token, but avoids getting to its substance. Apart from these factors, the summary amnesty legislation benefitting both former warring parties prevents the possibility of publicly discussing justice and pursuing war crimes. With Frelimo’s impressive, albeit amply contested, win of the 2019 elections at the national level and provincial tier of government, the paradigm of ‘winner takes all’ may come back into political reality, which in the past had triggered armed conflict and prompted political negotiations on some degree of power sharing through decentralization arrangements. In some senior political circles, this paradigm is now paraphrased as the introduction of a benevolent authoritarian African regime, at the cost of democratic checks and balances and a strong civil society. Under these circumstances, reconciliation initiatives as sketched above , primarily promoted by civil society in the broadest sense and including FBOs, would seem a viable strategy to breathe new life into the August 2019 agreement and opening space for the youth to actively engage the political parties which, up to today, they had talked peace but remained prepared for war. Only Chissano, in the aftermath of the Rome General Peace Accord, attempted to ‘walk the reconciliation talk’. The present constellation and the terrible consequences for lives and livelihoods in Cabo Delgado would also represent a strategic opportunity to become actively involved in peace consolidation, from which the Mozambican CSOs have been kept at a distance, leaving peace-making to political leaders only. A Malawian proverb suggests that he who thinks he is leading but has no followers is only taking a walk.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict - civil war / conflito - guerra civil; conflict / conflito

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

Conferência Internacional Sobre a Educação da Rapariga - ROSC (ROSC - Fórum da Sociedade Civil para os Direitos da Criança, 2019)
O Movimento de Educação para Todos (MEPT) em coordenação com o Ministério da Educação e Desenvolvimento Humano (MINEDH), realizou nos dias 6 e 7 de Junho do corrente ano, em Maputo, a Conferência Internacional Sobre a Educação da Rapariga com o lema “Desafios, Partilha de Experiências e Boas Práticas para Assegurar a Retenção da Rapariga no Sistema de Ensino.” Esta conferência tinha como objetivos: → Troca de experiências em torno de políticas e práticas existentes a nível nacional e internacional para assegurar a retenção da rapariga no sistema de ensino e discutir estratégias e possíveis soluções para a redução dos índices de abandono escolar por parte das raparigas na África Subsariana; → Apreciar os instrumentos e experiências existentes para prevenir a gravidez infantil e combater a violência baseada no género nas escolas a nível da região; → Olhar para os instrumentos e experiências existentes de boas práticas na região para o tratamento de casos de alunas grávidas nas escolas e a sua reintegração.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género

Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

IV Recenseamento Geral Da População E Habitação 2017: Resultados Definitivos - INE (Instituto Nacional de Estatística, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Como é do conhecimento geral, o Censo 2017 tinha por objectivo estabelecer o conhecimento estatístico, quantitativo e qualitativo, tão exacto quanto possível, da população moçambicana e de todos os demais residentes e presentes no território nacional, bem como do parque habitacional (Lei do Recenseamento, n.º 4/79 de 19 de Maio). O Censo 2017 foi realizado em todo o território nacional de 1 a 15 de Agosto de 2017. Os resultados disponibilizados através da presente publicação referem-se a 1 de Agosto desse ano (momento censitário, ou seja, referência temporal à qual a informação recolhida durante o recenseamento é relativa).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

IV Recenseamento geral da população e habitação 2017: resultados definitivos Moçambique - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística, Governo de Moçambique, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Esta publicação encontra-se estruturada em duas partes: • A primeira inclui principais conceitos e definições necessári os para a interpretação dos resultados; • A segunda é composta por quadros que foram definidos como prioritários para as publicações em suporte de papel.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Protecção social e poupança em 10 edicões dos desafios: que tipo de protecção social pode Moçambique desenvolver? - Siúta, Moisés S. (Desafios para Moçambique 2019, 2019)
Que tipo de protecção social poderá Moçambique desenvolver sem poupança interna e profundamente dependente da poupança externa? Esta é a questão principal que este artigo pretende discutir. A discussão é feita em dois sentidos: mostrar a importância da pesquisa dentro da qual a pergunta surgiu e mostrar a relevância da relação que a mesma estabelece entre a poupança e a protecção social. No primeiro sentido, a relevância da pesquisa é demostrada na abordagem das limitações e deficiências do sistema e formas de protecção social vigentes em Moçambique, destacando-se os elementos que podem contribuir para melhorar o sistema de protecção social moçambicano, abordados dentro do trabalho de pesquisa do IESE. Em geral, os resultados da pesquisa apontam como principal deficiência do sistema de protecção social em Moçambique a sua incapacidade de fornecer protecção digna aos cidadãos, que se socorrem das suas diversas formas (e.g.: demográfica ou financeira) e mecanismos de funcionamento (e.g.: familiar, comunitário, financeiro público e privado). No segundo sentido, a importância da pergunta principal do artigo é fundamentada teórica e empiricamente por meio da identificação das relações existentes entre a protecção social e a poupança e da forma como essas relações se manifestam no caso particular em Moçambique. Por exemplo, o artigo discute o quadro teórico de análise do papel da poupança no crescimento e desenvolvimento económico (figura 1) e a forma como este influencia e determina o tipo, as formas e a qualidade da protecção social que Moçambique pode oferecer aos seus cidadãos. Além do quadro teórico, recorrendo a dados empíricos dos países do mundo inteiro, busca-se enquadrar a economia e o sistema de protecção social moçambicano e estabelecer a relação entre o tipo, as formas e a qualidade da protecção social com o nível de poupança, crescimento e desenvolvimento económico.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; poverty / pobreza; social protection / proteção social; ⛔ No DOI found

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Mozambique Country Strategy Paper 2018 -2022. Supporting Mozambique towards the HIGH5s - Santos, Almeida (African Development Bank, 2018)
The African Development Bank Group’s Country Strategy Paper (CSP) 2018-22 for Mozambique comes at a time when the country adopted its long term development strategy ‘ENDE’ 2015-35. The CSP was prepared on the basis of extensive consultations held with the Government of Mozambique, Development Partners, the private sector and the civil society. The main objective of the ENDE is the improvement of the livelihoods of the population through the structural transformation of the economy, and the expansion and diversification of national production. The strategy is to be implemented through the 5-Year Government Programs (PQGs). The PQG goal for 2015-19 is to increase employment, productivity and competitiveness to improve living conditions of Mozambicans, in an environment of peace, harmony and tranquillity, while consolidating democracy and inclusive participatory governance.
Keywords: G - Mozambique / Moçambique; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 Folheto (Brochure) - INS (2018)
O objectivo do IIM 2018 é disponibilizar as estimativas de indicadores demográficos e de saúde básicos, relacionados com a malária. As informações recolhidas através do IIM 2018 destinam-se a ajudar os decisores políticos e gestores do programa de controle de malária na avaliação e concepção de estratégias para melhorar a saúde da população do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA) 2015 - Ministério da Saúde- MISAU; Instituto Nacional de Estatística - INE; ICF (MISAU/Moçambique, INE, and ICF, 2018)
O presente relatório resume os resultados do Inquérito de Indicadores de Imunização, Malária e HIV/SIDA em Moçambique (IMASIDA 2015), conduzido pelo Instituto Nacional de Saúde (INS) do Ministério da Saúde (MISAU), em colaboração com o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através do Programa de Inquéritos Demográficos e de Saúde (Programa DHS). A assistência técnica adicional foi proporcionada pelo CDC (Centers for Disease Control and Prevention) dos Estados Unidos da América, através do seu escritório em Moçambique. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos para o Controlo da Malária (PMI), Fundo Global (FG-Rondas 8 e 9), Organização Mundial de Saúde (OMS), Fundo das Nações Unidas para a Infância (UNICEF), Aliança Internacional para a Saúde/Universidade de Washington (HAI/UW), Fundo das Nações Unidas para a População (FNUAP), Conselho Nacional de Combate ao HIV e SIDA (CNCS), através do seu Fundo Comum e Plano de Emergência do Presidente dos Estados Unidos para o Alívio da SIDA (PEPFAR), através do CDC.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

The political economy of corridors, commercialisation and agrarian change in eastern Africa - Scoones, Ian; Smalley, Rebecca (IESE Conference - Challenges of social and economic research in times of crisis, 2017)
The political economy of agricultural growth corridors: some first thoughts: • Neither state-driven ‘high modernism’ (Scott) nor enclave capitalism (Ferguson), but context-specific hybrid dynamic. • Endogenous capital and dynamics of accumulation crucial: diverting, upsetting , recasting grand plans and investments. • Contested visions of ‘development’ and ‘progress’ being played out, challenging and reconfiguring authority, with tensions and contradictions among elite alliances. • The everyday politics of corridors: contentious local politics (and resistances) intersect with wider corridor politics, influencing outcomes. • Who wins and who loses depends on terms of incorporation, predicated on both contemporary politics, but also long-run historical antecedents
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas

Desafio da articulação entre os cidadãos e os Comités de Qualidade e Humanização dos Cuidados de Saúde como órgãos de representação da comunidade - Dias, José (Centro de Aprendizagem e Capacitação da Sociedade Civil, 2017)
O Ministério da Saúde reconhece os Comités de Qualidade e Humanização dos Cuidados de Saúde nas Unidades Sanitárias como a principal forma de diálogo e ligação entre os serviços de saúde e as comunidades. Os Termos de Referência revistos, afirmam que o Comité de Qualidade e Humanização das Unidades Sanitárias constitui uma equipa de assessoria e coordenação ao processo de implementação da actividades de qualidade e humanização no âmbito da Unidade Sanitária. Destina-se a empreender uma política institucional de resgate de valores humanitários e de garantia de qualidade nos serviços de saúde, em benefício dos utentes e trabalhadores através da gestão participativa. Contudo, o sector de saúde dispõe também da Carta dos Direitos e Deveres do Doente, como instrumento que, no nosso entendimento, define o padrão da prestação de serviços, de comportamento, e concede espaço ao cidadão, individual ou colectivamente, para a exigência directa de serviços de saúde de qualidade. A este último propósito, por exemplo, cabe ressaltar que no quadro do Direito 16 (Direito a apresentar sugestões, queixas e reclamações) é estabelecido que através dos canais disponibilizados pelas Autoridades Sanitárias, os doentes têm direito a apresentar, individual ou colectivamente, petições, sugestões, reclamações ou queixas sobre a organização e o funcionamento dos serviços de saúde; e de ter as suas queixas atendidas prontamente e de maneira equitativa (MISAU, 2011). O que se apreende do exposto é que enquanto os Comités de Qualidade e Humanização funcionam numa lógica essencialmente de Democracia Representativa, a Carta dos Direitos e Deveres do Doente se insere numa abordagem de Democracia Participativa, buscando promover uma cidadania activa do doente/cidadão na sua interacção directa com as unidades sanitárias. O nosso artigo problematiza e discute as dinâmicas de representação e de participação activa do cidadão no processo da prestação de serviços de saúde. A nossa base de discussão é fundamentada em evidências de 15 distritos de actuação do Centro de Aprendizagem e Capacitação da Sociedade Civil (CESC), onde funcionam os Comités de Qualidade e Humanização, por um lado, e se implementa a abordagem de Responsabilização Social, usando ferramentas tais como Cartão de Pontuação Comunitária, por outro.
Keywords: G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; citizenship & participation / cidadania e participação; health / saúde

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (NUPI political economy reports, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza

A Economia Política da Descentralização em Moçambique: Dinâmicas, Efeitos, Desafios - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
O livro aborda a questão da descentralização mediante uma abordagem multidisciplinar e multissectorial, considerando o ângulo visual de tipo político, assim como institucional, da administração pública ou da burocracia, da economia, das finanças (públicas) e da sociedade. O objectivo que se põe tem a ver com o relacionamento entre descentralização e democracia. Trata-se de um assunto conhecido e enfrentado várias vezes no debate próprio da ciência política: será que uma maior descentralização corresponde a um nível mais avançado de democracia? Moçambique é um País ainda novo, quanto à sua vida democrática. E o livro oferece um quadro claro da história da descentralização desde 1992 até hoje; entretanto, a tese de fundo é a seguinte: a classe política que sempre esteve no poder procurou sistematicamente travar ou limitar os processos de descentralização. Será que esta tese é aceitável? Será, sobretudo, que esta tese sai comprovada das evidências que o livro traz?
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Mozambique: Report 8/2016 Country Evaluation Brief - Tvedten, Inge; Orre, Aslak (Norwegian Agency for Development Cooperation (Norad), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Government Decentralization Program in Indonesia - Nasution, Anwar (ADBI, 2016)
Without much preparation, Indonesia, in 2000, at a stroke replaced the previous system of centralized government and development planning with a wide range of decentralization programs. The reforms gave greater authority, political power, and financial resources directly to regencies and municipalities, bypassing the provinces. The powers transferred include those of executing a wide range of responsibilities in the areas of health, primary and middle-level education, public works, environment, communication, transport, agriculture, manufacturing, and other economic sectors. At the same time, the government replaced the antiquated cash-based, single-entry system of public finance with a modern double-entry accounting system that uses a single treasury account; is performance based; and has transparent management of the public treasury, tight expenditure and financial controls with performance indicators, computerized reporting, and a tightly scheduled auditing system.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Mozambique: Growth Corridors - ARUP (Arup and Cities Alliance, 2016)
This report relates to urbanisation as it is currently happening in Mozambique. It explores the present situation of cities and the government’s planned urbanisation strategy. It also discusses how the country plans to transition to a majority urban population. The report also discusses the impact of the urbanisation strategy on the regional development of the country through the promotion of growth corridors. To discuss this message, Future Cities Africa has selected three cities along the Nacala Corridor - Tete, Nampula, and Nacala - to explore current urbanisation trends and to highlight key challenges these cities may face in the future. This report relates to urban growth corridors in Mozambique and represents one of four reports prepared for Future Cities Africa. Each report covers a specific country, its national urbanisation strategy and its specific regional planning typology. The other three reports include metropolitan cities in Ghana, secondary cities in Uganda, and regional cities in Ethiopia
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; urbanization / urbanização

Civil society organisations’ political control over Brazil and Japan’s development cooperation in Mozambique: More than a mere whim? - Chichava, Sérgio; Durán, Jimena (LSE Global South Unit, 2016)
This article aims to analyse and explain the reasons behind the CSOs’ strong criticism of the ProSavana programme. This will contribute toward: (1) understanding the role of Mozambican CSOs as actors regulating international development cooperation projects; (2) revealing the political and economic interests behind ProSavana, as a first step toward a more critical approach to trilateral cooperation; and (3) illustrating through this case how a partnership between Brazil and “traditional” donors actually works. Firstly, we will analyse the cooperation policies of Brazil and Japan in Mozambique, taking into account its evolution, actors, mechanisms and motives. Secondly, we will introduce ProSavana, examining the narratives and roles of Japan and Brazil in this programme. Thirdly, we will consider the engagement of CSOs from the three countries, their role in exerting a political check on the Brazilian and Japanese governments, investors, and companies, as well as their narratives and mechanisms of protest.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; civil society / sociedade civil; development partners / parceiros de cooperação

Social protection reform in Mozambique and the new basic social security strategy - Falange, Sergio; Pellerano, Luca (IPC-IG One Pager, 2016)
In the framework of efforts to fight extreme poverty and recognising the importance and need to protect the poor and vulnerable population, in 2007 Mozambique approved Law No. 4/2007 which structured social protection into three levels, including basic social security. In 2010 the first National Basic Social Security Strategy (ENSSB I) was approved for the period 2010–2014, including a set of old (e.g. the Basic Social Security Programme—PSSB) and new (e.g. the Productive Social Action Programme—PASP) non-contributory social protection programmes, all implemented by the National Institute for Social Action (INAS) under the policy guidance of the Ministry of Gender, Child and Social Action (MGCAS).
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Estrutura Geológica de Moçambique - Nogar Boca (2016)
Tema: Estrutura Geológica de Moçambique A estrutura geológica de Moçambique é resultado da interacção de vários processos, sobretudo os endógenos (internos) e exógenos (externos), que se fizeram sentir e ainda sentem-se na actual região da África Austral, onde Moçambique faz parte. Do ponto de vista geológico, Moçambique apresenta duas grandes unidades geológicas: Pré-câmbrico Fanerozóico
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; natural resources / recursos naturais

Mozambique Early Generation Seed Study - USAID (Scaling Seeds and Technologies Partnership in collaboration with The Rutgers University, 2016)
Seed systems in Mozambique There are three identified dominant seed systems in Mozambique, namely informal seed system (mainly farmer-saved seed), the intermediary (mainly administered by the NGOs and communitybased organizations) and the formal seed system that includes public sector and private sector (local and international seed companies). The farmer-saved and intermediary systems account for the bulk of seed volume transacted across the country (90%) focusing mainly on the local varieties. Although the adoption rate is relatively high for cassava, there is no vegetative seed certification system in place. There is no official sesame variety, despite an over three-fold increase in the last 12 years in terms of the total area allocated to this crop. Early generation seed systems by crop Six crops selected for the Mozambique EGS case study were maize (hybrid and OPV), rice, cowpea, groundnut, soybean and cassava
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

FIFTY YEARS OF TRADE POLICY IN INDONESIA: NEW WORLD TRADE, OLD TREATMENTS - Pangestu, Mari; Rahardja, Sjamsu; Ing, Lili Yan (Bulletin of Indonesian Economic Studies, 2015)
Indonesia's trade policy has evolved over the last 50 years. It has been influenced by the country's level of development and the conflict between openness and protectionism; external developments, such as commodity booms and busts and increased competition; and international commitments, whether multilateral or regional. As a result, trade policy has often been ambivalent and ineffective. Given that Indonesia has undergone various transformations and that the world is a different place from what it was in 1965, the country needs to take a more pragmatic and forward-looking stance. Trade policy needs to be part of a comprehensive strategy to improve competitiveness and diversify exports. If Indonesia is to be part of the new paradigm, where the production of goods and services is based on production networks and global value chains, its policy focus will need to shift from protecting and favouring sectors to promoting trade and industrial policies that encourage the flow of goods, services, and people.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Revoltas da fome: protestos populares em Moçambique (2008-2012) - Brito, Luís de; Chaimite, Egídio; Pereira, Crescêncio; Posse, Lúcio; Sambo, Michael; Shankland, Alex (Cadernos IESE, 2015)
Em Fevereiro de 2008 e Setembro de 2010, as cidades de Maputo e Matola foram palco de protestos violentos contra a subida do custo de vida, protagonizados por grupos de populares. Tais protestos foram logo depois replicados em algumas outras cidades do país, mas numa dimensão bem mais restrita e rapidamente controlados pelas forças policiais. Em Novembro de 2012, um novo protesto se desenhou, mas a acção repressiva imediata nos locais críticos de concentração dos populares pelas forças da polícia, que nos últimos anos tinha sido reforçada fortemente em homens e material, impediu que a violência se generalizasse, ainda que não tenha evitado a paralisia quase total da actividade no grande Maputo durante um dia e meio. Neste relatório procuramos mostrar que, se estas revoltas se enquadram num movimento mais amplo que desde 2008 tem abalado muitos países em consequência do aumento e da alta volatilidade dos preços alimentares no mercado internacional, elas exprimem sobretudo dinâmicas económicas locais e são um resultado da exclusão social e política a que são votadas as camadas sociais urbanas mais pobres em Moçambique. O relatório começa por apresentar uma breve perspectiva histórica e caracterização da natureza da economia moçambicana e da tradição política autoritária que tem sido dominante desde a proclamação da independência, ainda que coexistindo com uma profunda mudança nas alianças políticas do partido no poder, para depois abordar a questão alimentar e do custo de vida, assim como o contexto imediato dos protestos, os discursos e representações sobre os mesmos e o tipo de resposta por parte do governo.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

An Analysis of Mozambique’s Political and Economic Networks - Chivangue, Andes; Cortez, Edson (CEsA - research center part of CSG/Research in Social Sciences and Management, 2015)
This paper analyses the social networks existing among politicians and economists in contemporary Mozambique, using the SNA-Social Networks Analysis method to identify the links between these individuals, to discern their relationships and to measure both the density and the centrality of the political-business network. Mozambique’s political and business elite is thus identified. A network sociogram is presented identifying the individual position in the network and the linkages among these individuals and several positional metrics of the individuals in the network are estimated, allowing identifying each individual and its influence in the network. As this network is resource accumulation driven, this exercise permits to identify the main political and economic individual active in Mozambique economy. President Guebuza define the major network centre and other individuals, Joaquim Chissano, the former president, and Graça Machel, the widow of another former president. Policy implications are derived and the links between them displayed, allowing for an accurate view of Mozambique’s political and business world.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Gender in Political Economy Analysis - Browne, Evie (GSDRC, University of Birmingham, 2014)
This report provides a brief examination of how and where gender analysis is incorporated into Political Economy Analysis (PEA). An initial review of the literature indicates that gender is not systematically included in PEA. This was also conveyed by a number of experts consulted for this report, who stated that few if any PEAs to their knowledge had included a gender analysis, with the issue usually treated only in passing. The report nevertheless highlights the existing examples of gender-oriented analytical questions used in common PEA tools. It also identifies areas of overlap between gender and political economy analysis.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); gender / género

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

Moçambique Inquérito Demográfico e de Saúde 2011 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2013)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Juventude(s) e AIDS em Moçambique: Um Estudo Qualitativo no Distrito de Nhamatanda - Chicamisse, Francisco Armindo Zinhame (Universidade Federal de São Paulo, 2013)
O presente estudo pretende compreender como são desenvolvidas as ações de prevenção do HIV do Programa Geração Biz (PGB) direcionadas aos jovens dos 15-24 anos e, dessa forma buscar a compreensão da possível vulnerabilidade destes a infecção pelo HIV no distrito de Nhamatanda em Moçambique. Para o alcance deste desiderato baseei-me numa abordagem qualitativa, embasada no método etnográfico. No processo de coleta de dados privilegiei a observação participante, complementada por entrevistas semi-estruturadas e uma extensiva pesquisa bibliográfica. No distrito de Nhamatanda os jovens dos 15-24 anos constituem um dos segmentos populacionais mais afetados pelo HIV/AIDS, com uma taxa de prevalência estimada em 30,5% no ano de 2007, sendo por isso considerado um dos grupos mais vulneráveis a infecção pelo HIV. As ações de prevenção do HIV voltadas para este grupo são desenvolvidas pelo PGB, através das suas três componentes: escolar, comunitária e clínica. Entretanto, estas ações ainda estão assentadas na premissa de que a simples transmissão de informação implica na mudança de comportamentos dos jovens. Ademais, as ações de prevenção acabam tendo por vezes um caráter setorial e descontínuo, o que não permite o alcance de resultados mais duradouros no âmbito da prevenção do HIV. Os resultados deste estudo sugerem que as ações de prevenção do HIV ainda não se têm traduzido na redução considerável da referida vulnerabilidade dos jovens (15-24) a infecção pelo HIV neste distrito. Estas ações colocam por vezes os jovens em situações de maior suscetibilidade a infecção pelo HIV. Portanto, há uma necessidade de se repensar no modo como estas ações têm sido operacionalizadas, reelaborar os modelos pedagógicos que as norteiam e adequar os conteúdos semânticos das mensagens em função dos diferentes contextos socioculturais em que a epidemia se espraia.
Keywords: G - Mozambique / Moçambique; G - central / centro; GD - Nhamatanda; GP - Sofala; Health PEA; L - portuguese / português; access to services / acesso a serviços; health / saúde; youth / juventude

"Acção social produtiva" em Moçambique: Uma falsa solução para o problema real - Francisco, António (Desafios para Moçambique 2013, 2013)
O artigo está organizado em quatro secções. A primeira secção aborda a seguinte questão: “Qual é a essência do real problema que o conteúdo e a operacionalização da ASP não identifica correctamente?” Esta questão é respondida em dois momentos ou subcapítulos. Inicia-se por sublinhar a importância da distinção entre os principais meios de aquisição da riqueza para a identificação do problema real da sociedade moçambicana e relevante para o debate sobre a pobreza. De seguida, apresenta-se um breve enquadramento da protecção social formal moçambicana, com destaque para o quadro da actual ortodoxia oficial sobre a natureza e as causas da pobreza. A segunda secção reúne um conjunto de dados e relações empíricas, caracterizadoras da dimensão demográfica, económica e social do problema real da população moçambicana. Chama a atenção para a natureza das mudanças em curso na estrutura etária, manifestada no aumento da dependência infantil. Uma dependência que a população tenta compensar, através da participação activa em actividades económicas de todas as gerações: crianças-adolescentes, jovens/adultos e idosos. A terceira secção toma como referência a análise das secções anteriores, para demonstrar que uma solução errada para um problema errado é, por definição, duplamente errada e gratuita. De forma resumida, apresenta os objectivos, o que é e qual é o alcance da iniciativa ASP em curso; argumenta, de seguida, que a ASP não é social nem produtiva. A quarta secção contém algumas considerações finais e a conclusão. Explica porque não tem sentido fazer acompanhar a análise crítica da iniciativa ASP de uma proposta alternativa, visando convertê-la numa acção alegadamente mais produtiva do que tem sido. Respondendo à questão “Justifica-se a ASP?”, o artigo defende que a resposta depende da perspectiva de protecção social seguida; identifica algumas das respostas que têm sido dadas, desde a resposta do Governo, a qual se inspira ou está alinhada com a do Banco Mundial, até à do próprio autor deste texto. Após mostrar que a ASP oferece uma falsa solução para um problema real, o artigo termina identificando duas implicações desta constatação: uma política e outra social
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; social action / ação social; social protection / proteção social

The Effects of Sector Characteristics on Accountability Relationships in Service Delivery - Mcloughlin, Claire; Batley, Richard (Social Science Research Network, 2012)
Why do different services encounter particular constraints and opportunities in their delivery? This working paper identifies a set of characteristics that can be used to differentiate between services, and between functions within them, and asks how these defining or ‘fixed’ characteristics may influence key relationships of accountability and control.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - MAP Consult (2012)
The powerpoint has the same objective as the article (see related section). ------- The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; G - Mozambique / Moçambique; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; health / saúde

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social

Citizen voice and state accountability: towards theories of change that embrace contextual dynamics - Tembo, Fletcher (Overseas Development Institute, 2012)
The development industry is increasingly pushing practitioners to achieve results, and to do better in demonstrating what works, what does not, and explaining why. There is a growing interest in going beyond the measurement of results to being able to understand the basis for success or failure. Consequently, the development of explicit theories of change (ToCs) is starting to be viewed as central to this process, as a key part of what constitutes ‘rigour’ in impact evaluations. Citizen voice and accountability (CV&A) project interventions produce and reproduce diverse outcomes that are not amenable to linear models of ToCs. This paper uses a critical analysis of CV&A cases from the Mwananchi Governance and Transparency Fund (GTF) programme to examine how citizen voice and accountability happens in different governance contexts. The analytical framework used in this paper draws on the well-known tools of outcome mapping (OM) and political economy analysis (PEA). Key points: Enabling citizens to influence government accountability is a complex process involving political dynamics at the citizens’ interface with state institutions; Developing explicit theories of change (ToCs) from the start of programme planning helps planners delve into complex citizen–state dynamics; and Fusing political economy analysis and outcome mapping tools can help develop a deeper understanding of these dynamics to generate more effective ways to achieve outcomes.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; civil society / sociedade civil

Estender a cobertura da protecção social num contexto de alta informalidade da economia: necessário, desejável e possível? - Cunha, Nuno; Orton, Ian (Cadernos IESE, 2011)
Este artigo coloca em debate a extensão da cobertura da protecção social num contexto de alta informalidade da economia, questionando se ela é necessária, desejável e possível. Segundo os autores existem vários factores que justificam considerar-se a expansão da protecção social desejável, começando pelo facto de ser um elemento importante para o processo de construção de um estado, considerando o seu impacto em termos de promoção da coesão social. Outros factores têm a ver com o seu contributo para a redução da pobreza e exclusão social, impacto em dimensões do capital humano como a saúde, nutrição e educação, o seu contributo potencial para a produtividade e para desenvolvimento económico. O artigo apresenta alguns exemplos diversificados de como diferentes países (incluindo países Africanos) têm encontrado diferentes soluções para atingir o objectivo da extensão da cobertura. Contudo, defende também que os programas de Protecção Social (PS) não constituem, em si, um milagre que possa erradicar por si só a pobreza. Para que tais programas possam ter um contributo real na redução da pobreza é necessário que eles sejam integrados num quadro global de política de desenvolvimento socioeconómico, onde o aumento da produtividade, da competitividade, do acesso aos serviços de saúde e educação, entre muitos outros, terão de continuar a ser articulados. O artigo defende ainda que muitas vezes não são as questões económicas que determinam o investimento em PS, mas são as opções políticas (em termos de modelo de desenvolvimento social e económico), em particular as opções que estão associadas a questões de redistribuição, fiscalidade e de combate à pobreza, que terão o peso decisivo nas opções a ser tomadas em termos de extensão da protecção social. São avançadas algumas ideias para reflexão sobre o papel que a protecção social poderia desempenhar num processo de desenvolvimento mais inclusivo, com especial incidência sobre a realidade moçambicana, e apresentadas algumas sugestões sobre as quais os stakeholders poderiam debruçar-se.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; social protection / proteção social

Ten years of single window implementation: lessons learned for the future - Koh, Jonathan (Global Trade Facilitation Conference 2011, 2011)
This paper examines the Single Window concept and its developments in practice over the last 10 years and provides an analysis of its development over time. An overview of the emerging information technology that would impact its future development is also presented. The paper also examines regional trends in Single Window implementation, based on a survey of tenders documents issued by various countries in the recent years. Finally, it offers an outlook on its future development and provides a number of recommendations.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Local economic governance: a survey of business operators in 245 districts/municipalities in Indonesia, 2011 - The Asia Foundation; Regional Autonomy Watch (Local Economic Governance, 2011)
Decentralization has been underway in Indonesia for more than ten years, but recently many have challenged the how effectively decentralization – and even democratization – is being implemented. Deterioration in the quality of public services, the many corruption cases involving local governments, and low economic growth rates in some regions have prompted discourse about whether the country is making a reversal away from decentralization and democratization. We recognize that the move toward regional autonomy has not been without its faults. Nevertheless, a choice was made to strengthen democracy and move towards local autonomy based on the problems created by the centralistic, authoritarian system of the previous regime. Yet it is unfair to judge regional autonomy a failure after it has been implemented for such a short time, and under a somewhat inconsistent policy framework. Since 2001, the Regional Autonomy Watch (KPPOD) and The Asia Foundation have aimed to present a clear picture of the quality of regional economic governance from the perspective of business owners. Our studies provide input to government at the central, provincial and regional/municipal levels, as well as information to other stakeholders regarding efforts that can be undertaken to promote improve economic growth under regional autonomy. This year’s study finds significant variation among regions in the quality of economic governance. This indicates that despite many limitations, some regions have used the opportunities provided by autonomy to foster good governance while others have not. It is hoped that this present study, and the awards presented to regencies and municipalities with the best performance, will promote a healthy competition among regional leaders. It is also envisioned that local governments whose performance is still low can learn from their neighbors who are doing better, and be inspired to improve. We recognize that improving economic governance requires a strong commitment and hard work, not only from the heads of regions but from all ranks of government officials, politicians, business owners and other stakeholders. This study can help set priorities for reform of local economic governance, identifying areas for immediate improvement that are relatively easy to achieve but have the potential of significant impact. Other aspects may need more time for improvement.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; M - survey / inquérito; Northern PEA; decentralization / descentralização

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

Social Protection in Mozambique: A new imperative? - Waterhouse, Dr Rachel; Lauriciano, Gil (IESE Conference ‘Poverty Dynamics and Patterns of Accumulation in Mozambique, 2009)
Even before the impact of a global economic crisis kicks in, there is renewed thinking in Mozambique about a wider role for the state in social protection. Proponents are still struggling to convince others of the economic and social value of a broader investment in social protection. This is against the backdrop of institutional resistance borne of Mozambique’s political and economic history. The government attitude to social protection has been influenced by colonial experience of an extractive rather than protective state and the legacy of post-Independence events and processes. After Independence in 1975, initial social service expansion was heavily undermined by war-time destruction and economic collapse in the 1980s. Post war, the Government’s top priorities were to re-establish security and rebuild infrastructure. However, political and economic liberalisation in the 1990s saw tight caps on state spending. Poverty was so widespread and deep that there seemed to be little scope for special consideration of the ‘poorest of the poor’... except for ad hoc initiatives, such as the food subsidy programme for the poor and unable to work. In the last 15 years, Mozambique has experienced impressive economic growth and poverty reduction. Nonetheless Mozambique continues to rank amongst the world’s poorest countries. Government is becoming more aware of chronic poverty and that large population groups are currently unable to escape the poverty trap. This raises debate about what can be done ... and promotes renewed thinking on social protection. There are still many obstacles to a coherent and comprehensive approach to social protection. These include: analytical limitations around the causes, consequences and extent of vulnerability as well as the potential social and economic benefits of social protection; institutional barriers; budgetary limitations; and perceived political risk. However, there is also a growing acceptance of the relevance and importance of social protection to reduce vulnerability, build resilience and contribute to poverty reduction. These issues need to be addressed at policy and practical level, if Mozambique is to effectively address the growing challenge of chronic poverty.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; poverty / pobreza; social protection / proteção social

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

The politics of gradualismo: popular participation and decentralised governance in Mozambique - Buur, Lars (Rethinking Popular Representation., 2009)
The question of how to proceed with democratic decentralisation has been of political concern in Mozambique over the past decade. In accordance with post-war constitutional commitments to démocratisation after the country’s post-independence flirtation with socialism and a high degree of centralism, the process of decentralisation has taken two forms. First, a system of locally elected governments in the form of municipalities (municipios) for the urban and semi-urban areas was approved in 1997 to cover the devolution of direct although limited powers and functions to autonomous elected bodies. The Municipal Law (2/1997) made provision for locally elected municipalities (autarquias locais) in 33 urban or peri-urban settings.1 Second, for the rest of the population (roughly .70 percent) and the local state administration, the process of decentralisation has taken the general form of de-concentration and a transfer of responsibility to lower level bodies within the state sector combined with different forms of participatory mechanisms for representation and consultation. These participatory mechanisms are grounded in community- based organisations claiming representative status on the basis of identity, interest, community, and similar factors.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; governance / governação

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência

Adverse incorporation, social exclusion and chronic poverty - Hickey, Samuel; Andries du Toit (Institute for Development Policy and Management, School of Environment and Development, University of Manchester, 2007)
There are a number of compelling reasons to focus on the ways in which the processes and relations of adverse incorporation and social exclusion (AISE) underpin chronic poverty. In particular, AISE research draws attention to the causal processes that lead poverty to persist, and to the politics and political economy of these processes and associated relationships over time. Specific dimensions of AISE are explored in relation to chronic poverty – namely political, economic, socio-cultural and spatial – and are found to relate closely to long-term historical processes, particularly concerning the nature and forms of capitalism, different stages and types of state formation, and institutionalised patterns of social norms and attitudes. However, it is also stressed that much of the promise of AISE research lies in its capacity to cross analytical boundaries and capture the multi-dimensional and interlocking character of long-term deprivation. This analysis suggests a number of fruitful areas for research, most of which are currently under-explored in poverty research. In methodological terms, there are benefits to adopting integrated qualitative-quantitative approaches when investigating AISE, although it is argued that (a) the relational nature of AISE and the limitations of quantitative data may dictate that qualitative work should take priority here and (b) that more historical and theoretically oriented forms of research are particularly appropriate in studying AISE. To think about challenging AISE involves shifting the frame from policy to politics and from specific anti-poverty interventions to longer-term development strategies, particularly in terms of industrialisation and labour market restructuring, moves towards developmental states and supporting shifts from clientelism to citizenship. However, a range of more immediate development policy interventions may also be able to make headway in challenging the forms of AISE that perpetuate poverty.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Gender, Entrepreneurship, and Competitiveness in Africa - Bardasi, Elena; Blackden, Mark C.; Guzman, Juan (World Bank, 2007)
This chapter aims to shed light on the nature of men’s and women’s enterprises in Africa, to assess the extent to which the constraints and obstacles faced by women and men entrepreneurs may differ, and to address whether the constraints and obstacles entrepreneurs face affect the productivity and performance of men’s and women’s businesses differently.We begin with a brief overview of gender in the economy, followed by a more detailed analysis of available Enterprise Survey data where key characteristics of businesses can be disaggregated by the sex of the business owner.1 This allows us to look at various characteristics of men’s and women’s businesses, including perceptions of obstacles and constraints, and to assess productivity differences.After briefly placing this analysis in a wider context, the chapter concludes with some recommended actions to address the gender dimensions of entrepreneurship more systematically in policy and programs aimed at supporting private-sector development, along with suggestions for further data collection and analysis.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

State Recognition and Democratization in Sub-Saharan Africa: A New Dawn for Chiefs? - Buur, Lars; Kyed, Helene Maria (Governance, Security and Development, 2007)
State Recognition and Democractization in Sub-Saharan Africaآ explores the link between liberal-style democratization and state recognition of traditional authority in Sub-Saharan Africa. Being critical and empirically grounded, the book explores the complex, often counter-balancing consequences of the involvement of traditional authority in the wave of democratization and liberal-style state-building that has rolled over sub-Saharan Africa in the past decade. It scrutinizes how, in practice, traditional leaders are being drawn into governance in Mozambique, Zambia, Namibia, Malawi, Burkina Faso, and the Somali region of Ethiopia, and relates these developments to state governance in the declining democracy of Zimbabwe and the emerging state of Northern Somalia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; authority / autoridade; decentralization / descentralização; governance / governação

Gender and economic growthin Kenya: unleashing the power of women - Ellis, Amanda; Cultura, Jozefina; Dione, Nouma; Gillson, Ian; Manuel, Clare; Thongori, Judy (The World Bank, 2007)
This report examines the legal, administrative, and regulatory barriers that are preventing women in Kenya from contributing fully to the Kenyan economy. Building on the 2004 Foreign Investment and Advisory Service (FIAS) report, “Improving the Commercial Legal Framework and Removing Administrative and Regulatory Barriers to Investment,” this study looks at the bureaucratic barriers facing women in Kenya through a gender lens. The report makes specific recommendations to address gender-related barriers in the context of ongoing government and donor initiatives to encourage private sector development as the key driver of poverty reduction and economic growth, in line with Kenya’s Economic Recovery Strategy for Wealth and Employment Creation 2003–2007 (ERS). Addressing these constraints will not only allow women to make a full contribution to the economy but also improve their livelihoods and those of their families and help create a more enabling environment for all businesses in Kenya.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; gender / género; justice / justiça

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

Business licensing and one stop shops in Indonesia - Steer, Liesbet (The Asia Foundation, 2006)
In 2001, Indonesia embarked on a decentralization process that has had a dramatic impact on the local political landscape, especially in relation to taxation and administrative processes. Rules and procedures that govern licensing, registration, some taxes and user charges have largely been devolved to local governments. A significant number of new licenses and charges have been created at the local level, and most licenses are issued through a complicated system of procedures and agencies. Licensing has become one of the most important barriers to business formalization and growth in Indonesia. The local licensing framework in Indonesia has three key problems, raising transactions costs and inefficiencies. Licensing reform through One Stop Shops (OSS). The Asia Foundation OSS technical assistance program. The methodology has proven to be highly effective.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Impacto da Economia Informal na Protecção Social, Pobreza e Exclusão: A Dimensão Oculta da Informalidade em Moçambique - Francisco, António A da Silva; Paulo, Margarida (CRUZEIRO DO SUL – INSTITUTO DE INVESTIGAÇÃO PARA O DESENVOLVIMENTO JOSÉ NEGRÃO, 2006)
O trabalho anunciado no título desta monografia analisa a economia informal e a protecção social, bem como os seus impactos, directos e indirectos, no desenvolvimento económico e humano, na pobreza e na exclusão social em Moçambique. A resposta e os resultados que a monografia encontrou para as questões principais de pesquisa revelaram-se, de algum modo, surpreendentes, tanto para os promotores do estudo como para os organizadores e os próprios autores. A surpresa não é por causa da revelação que a informalidade domina a sociedade moçambicana. Afinal de contas, os números aqui reunidos, segundo os quais a economia informal domina 90% da economia de Moçambique, apenas confirmam o que as pessoas sentem e vivem na sua vida quotidiana. As surpresas reveladas neste trabalho têm a ver com os mitos e falácias em que as pesquisas sobre economia informal em Moçambique têm acreditado. Do ponto de vista analítico e prático, a presente monografia levanta um duplo desafio, um relacionado directamente com a economia informal e o outro com a protecção social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social Protection PEA; economic development / desenvolvimento económico; employment / emprego; informality / informalidade; poverty / pobreza; social protection / proteção social

Moçambique Inquérito Demográfico e de Saúde 2003 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2005)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Power, livelihoods and conflict: case studies in political economy analysis for humanitarian action (Humanitarian Policy Group, Overseas Development Institute, 2003)
What can political economy analysis contribute to humanitarian aid interventions? How can agencies undertake such analysis in difficult environments? This chapter introduces the findings of a study (2001-2002) of four cases: Afghanistan, the eastern Democratic Republic of the Congo (DRC), Sierra Leone and the Casamance in Senegal. Political economy analysis is best conducted alongside existing humanitarian operational activities via integration into existing analytical tools.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; power / poder

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género

What Happens to the State in Conflict?: Political Analysis as a Tool for Planning Humanitarian Assistance - Cliffe, Lionel; Luckham, Robin (Disasters, 2000)
It is now part of received wisdom that humanitarian assistance in conflict and post-conflict situations may be ineffective or even counterproductive in the absence of an informed understanding of the broader political context in which so-called ‘complex political emergencies’ (CPEs) occur. Though recognising that specific cases have to be understood in their own terms, this article offers a framework for incorporating political analysis in policy design. It is based on a programme of research on a number of countries in Africa and Asia over the last four years. It argues that the starting-point should be an analysis of crises of authority within contemporary nation-states which convert conflict (a feature of all political systems) into violent conflict; of how such conflict may in turn generate more problems for, or even destroy, the state; of the deep-rooted political, institutional and developmental legacies of political violence; and of the difficulties that complicate the restoration of legitimate and effective systems of governance after the ‘termination’ of conflict. It then lists a series of questions which such an analysis would need to ask — less in order to provide a comprehensive check-list than to uncover underlying political processes and links. It is hoped these may be used not only to understand the political dynamics of emergencies, but also to identify what kinds of policy action should and should not be given priority by practitioners.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; governance / governação

'Dhlakama É Maningue Nice!': An Atypical Former Guerrilla in the Mozambican Electoral Campaign - Cahen, M. (Transformation, 1998)
Despite significant problems with urban criminal gangs and highway robbers, Mozambique is a country at peace since 4 October, 1992. Under the auspices of the Italian religious congregation of Santo Egidio,4 Joaquim Alberto Chissano, president of the Republic and of the Frente de libertagao de Mozambique (FRELIMO), once the 'Marxist-Leninist' single-party of the country, and Afonso Dhlakama, president of the Resistencia national de Mogambique (RENAMO), the former guerrilla group and longtime recipient of aid from South Africa, signed the 'General Peace Accord' on that date. This agreement has never seriously been called into question. During the first 15 days following the accord there were a number of incidents. For example, it contained provisions for maintaining each party's administration in their part of the country, but did not specify the zones belonging to one party or the other. As a result, a number of RENAMO regional commanders sought to occupy areas that they had not previously controlled, the largest one being Angoche in Zambezia. It appears that they had told Afonso Dhlakama that they already held these areas, and following the peace accords, they urgently sought to gain real possession of the territory in question.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict / conflito; ⛔ No DOI found

Ethnicity, Politics, and History in Mozambique - Alpers, Edward A. (Indiana University Press, 1974)
Conclusion Of course, the political disgrace of Joana Simiao does not by itself solve the problem of Makua-Lomwe separatism, any more than the collapse of the Movement for a Free Mozambique has solved the larger problems of national reconstruction in Mozambique. But by now it should be clear to all that the only political movement qualified to achieve that goal is FRELIMO, who demonstrably are working for the interests of all Mozambicans and who enjoy the support of Mozambicans of all races, religions, and ethnic backgrounds, including both Makua-Lomwe and Maconde. During its decade of armed struggle FRELIMO has successfully defended its just cause against attack from without and dissension from within. In the process it has painstakingly built a truly national liberation movement. The lessons learned in that crucible, which se suddenly belongs to the past, must now be applied to the future
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; politics / política; ⛔ No DOI found

GFF Political Economy of Health System Reforms
This webinar provided the unique opportunity to hear from and exchange with Dr. Muhammad Pate, (Director of the Global Financing Facility and Global Director of the Health, Nutrition and Population Global Practice of the World Bank) on the political economy of health system reforms and, particularly, on the transformative approach of the GFF. Summary Note Video
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); development partners / parceiros de cooperação; health / saúde

Political Economy Assessments at Sector and Project Levels (2011-03)
How-to guide on PEAs and why to conduct them
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP)

Islamic Radicalization in Northern Mozambique: The Case of Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Cadernos IESE)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui. ----- This research report is a first attempt to address the phenomenon in order to understand the complexity of the dynamics not only in the origin of the Al-Shabaab group but also in the structure of the conflict and violence in Cabo Delgado. Almost two years after the first attack on Mocímboa da Praia (5 October 2017), the phenomenon has been the subject of multiple interpretations, from the (at least public) Mozambican government’s preferred thesis of a conspiracy driven by external forces opposed to Mozambique’s development, through the land conflict against the backdrop of the area’s natural resources thesis, to the sect (Morier-Genoud, 2019) and jihadism theses, in the context of the growing dynamics of violent extremism in the countries of the region i.e. Tanzania, Kenya and the Great Lakes region. While highlighting this last thesis (jihadism), our exploratory research has shown that the phenomenon is complex and requires profound multidisciplinary research that takes into account a multiplicity of historical, social, political, economic and religious factors. This is why, rather than draw conclusions, this report ends with a series of questions: • Why is Mocímboa da Praia the epicentre of the phenomenon? • How does the Mozambican state deal with the proliferation of religious institutions in the country? • What are the implications of the Islamic radicalization phenomenon for investments in the country’s northern region? To what extent can these investments heighten or reduce local cleavages and contribute to Islamic radicalization phenomenon? • To what extent does the Islamic radicalization phenomenon affect current efforts to stabilize the country politically and economically? • To what extent can regional dynamics (Tanzania, Kenya, Great Lakes region) influence the evolution of the phenomenon in Mozambique? • What kind of policies (including security) does the country need to address the phenomenon? • What lessons does the phenomenon bring to the state-building process in Mozambique? These questions feed into the ongoing research program at the Institute for Social and Economic Studies (IESE) since early 2019, involving researchers from IESE and other research centres, entitled “State, Violence and Development Challenges in Cabo Delgado”.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Subnational HDI - Global Data Lab - Iñaki Permanyer; Jeroen Smits (Global Data Lab - Nijmegen Center for Economics (NiCE), Institute for Management Research, Radboud University)
Subnational Human Development Index - Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia

Quadros_PIB provincial 2011-2019.pdf — Instituto Nacional de Estatistica - INE (INE)
Produto Interno Bruto (PIB) de Moçambique por Regiões, Províncias e País, 2011-2019
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; economic development / desenvolvimento económico

Deviations between the Planned and the Execution Undermine the Health Budget – Observatório do Cidadão para Saúde - Observatório Cidadão para Saúde
In Mozambique, health services are mostly provided by the public sector, and it is the responsibility of the Ministry of Health (MISAU) to enable the creation, planning and control of national health policies. The health sector is the third sector that absorbs most resources from the State Budget (OE), followed by the Education and Infrastructure sectors, according to the methodology presented in the budget documents related to the economic and social sectors. This sector is divided into three levels: namely, the Central Level, which is represented by MISAU; The Provincial Level, which is represented by the Provincial Health Directorates (DPS); and Finally, we have the District Level, which is represented by the Health, Women and Social Action Secretariats (SDSMAS). Therefore, it will be based on these levels that our analysis of allocations to the health sector in the period from 2015 to 2020 will be undertaken.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; health - health services / serviços de saúde

Mozambique HDI Data - UNDP
Access and explore human development data for 191 countries and territories worldwide. Select Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia